Usability from Requirements Engineering to Interaction Design: A Qualitative Study on the USINN and USARP Approaches - Ramos, Hanna Ranielly da Silva; Sousa, Francisco; Pinheiro, Valéria Maria da Silva; Marques, Anna Beatriz (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2024)
The specification of usability requirements allows usability to be considered in the following stages of software development. This strategy prevents usability issues and reduces the rework required to correct these problems. One way to integrate usability requirements into interaction design is by adopting interaction and navigation modeling. Therefore, it is relevant to investigate approaches that promote usability, from requirements engineering to interaction design. This article presents an exploratory qualitative study using the USARP (USAbility Requirements with Personas and User Stories) method to elicit and specify usability requirements and the USINN (USability-oriented INteraction and Navigation) notation for interaction modeling. The research explores the benefits and challenges of adopting these approaches in a practical experience. The results indicated that USARP was a significant resource for mitigating the difficulties of modeling usability aspects with USINN, providing a solid foundation for modeling. By analyzing the USINN diagrams created by eight participants during a practical experience, we noted that some usability aspects specified by USARP could not be represented in interaction diagrams but in user interface prototypes, such as change of contrast, highlighted messages, emphasis on buttons, and links. Despite these aspects, more than 80% of the participants modeled the user actions, systems responses, system status, success, and failing messages, progress feedback specified as usability requirements. Thus, the diagrams have a high level of completeness. However, a more precise mapping is still needed on how the usability requirements elicited with USARP can be modeled with the USINN notation.